2015
DOI: 10.1088/0004-637x/805/1/31
|View full text |Cite
|
Sign up to set email alerts
|

The Global Star Formation Laws of Galaxies From a Radio Continuum Perspective

Abstract: We study the global star formation law -the relation between gas and star formation (SF) rates in a sample of 181 local galaxies with infrared (IR) luminosities spanning almost five orders of magnitude (10 7.8 − 10 12.3 L ⊙ ), which includes 115 normal spiral galaxies and 66 (ultra)luminous IR galaxies [(U)LIRGs, L IR ≥ 10 11 L ⊙ ]. We derive their atomic, molecular gas and dense molecular gas masses using newly available HI, CO and HCN data from the literature, and SF rates are determined both from total IR (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 167 publications
(197 reference statements)
14
96
1
Order By: Relevance
“…Our results are consistent with the correlation between the IR and the HCN (1-0) luminosities shown in Gao & Solomon (2004a). Moreover, a tight linear correlation between the surface densities of the dense molecular gas and the SF rates, as well as between the HCN luminosity and the radio continuum luminosity, has been established for a large sample of galaxies (e.g., Liu & Gao 2010;Chen et al 2015Chen et al , 2017Liu et al 2015b). All of these results indicate that the star formation is very likely physically related to the dense molecular gas.…”
Section: Comparison Of Correlations Between the Ratiossupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with the correlation between the IR and the HCN (1-0) luminosities shown in Gao & Solomon (2004a). Moreover, a tight linear correlation between the surface densities of the dense molecular gas and the SF rates, as well as between the HCN luminosity and the radio continuum luminosity, has been established for a large sample of galaxies (e.g., Liu & Gao 2010;Chen et al 2015Chen et al , 2017Liu et al 2015b). All of these results indicate that the star formation is very likely physically related to the dense molecular gas.…”
Section: Comparison Of Correlations Between the Ratiossupporting
confidence: 90%
“…A least-squares fit and a Spearman test yield log(L IR /L′ HCN (4-3) )=2.1(±0.5) log( f 70 /f 100 ) + 3.8 (r s =0.50, p-value=3.5×10 ), respectively, indicating that there is a statistically significant correlation between L IR /L′ dense and T d . These correlations are slightly stronger than the correlation between L IR /L′ HCN (1-0) and f 60 μm /f 100 μm , but not as strong as the L IR /L′ CO (1-0) versus f 60 μm /f 100 μm correlation (correlation coefficient of 0.85; see Figure 9 in Gao & Solomon 2004a;Liu et al 2015b).…”
Section: Variation In the Infrared-molecular Line Luminosity Ratiomentioning
confidence: 86%
See 1 more Smart Citation
“…The two green points (triangles) are from Chen et al (2015), who observed M51 with 1 kpc resolution; the higher point is for the outer galaxy and the lower point is for inner (r < 1.66 kpc) part of M51. The blue point (pentagon) represents the whole, normal galaxies while the cyan point (hexagon) represents the whole (U)LIRGs, both from Liu et al (2015).…”
Section: Comparison To Extragalactic Resultsmentioning
confidence: 99%
“…The (U)LIRGs in Liu et al (2015) are again plotted in cyan, but only one value of conversion from HCN emission to dense gas mass was used by Liu et al (2015). Observations of HCN in M51 with a resolution of 1 kpc bridge the gap between the Milky Way clouds and whole galaxies.…”
Section: Comparison To Extragalactic Resultsmentioning
confidence: 99%